Commercial Gold Nanoparticles on Untreated Aluminum Foil: Versatile, Sensitive, and Cost-Effective SERS Substrate - Gudun, Kristina; Elemessova, Zarina; Khamkhash, Laura; Ralchenko, Ekaterina; Bukasov, Rostislav (Journal of Nanomaterials, 2017)
We introduce low-cost, tunable, hybrid SERS substrate of commercial gold nanoparticles on untreated aluminum foil (AuNPs@AlF). Two or three AuNP centrifugation/resuspension cycles are proven to be critical in the assay preparation.The limits of detection (LODs) for 4-nitrobenzenethiol (NBT) and crystal violet (CV) on this substrate are about 0.12nM and 0.19 nM, respectively, while maximum analytical SERS enhancement factors (AEFs) are about 107. In comparative assays LODs for CV measured on AuNPs@Au film and AuNPs@glass are about 0.35 nM and 2 nM, respectively. The LOD for melamine detected on AuNPs@ Al foil is 27 ppb with 3 orders of magnitude for linear response range. Overall, AuNPs@AlF demonstrated competitive performance in comparison with AuNPs@Au film substrate in SERS detection of CV, NBT, andmelamine. To check the versatility of the AuNPs@AlF substrate we also detectedKNO3 with LODs of 0.7mMand SERS EF around 2 × 103, which is on the same order with SERS EF reported for this compound in the literature.
Keywords: substrate; nanoparticles; aluminum foil